Homozygous pathogenic variant in BRAT1 associated with nonprogressive cerebellar ataxia - Mahjoub, Areej; Cihlarova, Zuzana; Tétreault, Martine; MacNeil, Lauren; Sondheimer, Neal; Caldecott, Keith W; Hanzlikova, Hana; Yoon, Grace; Care4Rare Canada Consortium (Neurology. Genetics, 2019)
OBJECTIVE: To investigate the pathogenicity of a novel homozygous BRAT1 variant in 2 siblings with nonprogressive cerebellar ataxia (NPCA) through functional studies on primary and immortalized patient cell lines. METHODS: BRAT1 protein levels and ataxia-telangiectasia mutated (ATM) kinase activity in patient-derived and control cell lines were assessed by Western blotting. The impact of the novel BRAT1 variants on mitochondrial function was also assessed, by comparing patient and control cell lines for rates of oxygen consumption and for phosphorylation (S293) of the E1⍺ subunit of pyruvate dehydrogenase (PDH). RESULTS: Two male siblings with NPCA, mild intellectual disability, and isolated cerebellar atrophy were found to be homozygous for a c.185T>A (p.Val62Glu) variant in BRAT1 by whole exome sequencing. Western blotting revealed markedly decreased BRAT1 protein levels in lymphocytes and/or fibroblast cells from both affected siblings compared to control cell lines. There were no differences between the patient and control cells in ATM kinase activation, following ionizing radiation. Mitochondrial studies were initially suggestive of a defect in regulation of PDH activity, but there was no evidence of increased phosphorylation of the E1⍺ subunit of the PDH complex. Measurement of oxygen consumption rates similarly failed to identify differences between patient and control cells. CONCLUSIONS: Biallelic pathogenic variants in BRAT1 can be associated with NPCA, a phenotype considerably milder than previously reported. Surprisingly, despite the molecular role currently proposed for BRAT1 in ATM regulation, this disorder is unlikely to result from defective ATM kinase or mitochondrial dysfunction.